Wagner's hypothesis in Europe: A causality analysis with disaggregated data - Ivan D. Trofimov (European Journal of Government and Economics (EJGE), 2023)
This paper examines Wagner hypothesis of the growth of public expenditure alongside the growth of economic activity for a panel of 28 European economies during the 1995-2018 period. The hypothesis is verified using Pesaran (2007) panel unit root and Westerlund (2007) cointegration tests that account for cross-sectional dependence in the series, and three panel causality tests (Toda-Yamamoto, Dumitrescu-Hurlin and Juodis-Karavias-Sarafidis) that are suitable for mixed order of series' integration, heterogeneous balanced panels and cases of limited evidence of cointegration. The empirical results suggested that expenditure and output variables were non-stationary in levels and stationary in the first differences; the cointegration among the variables was present; the causality was principally uni-directional (from output to public expenditure), in line with Wagner's hypothesis, or bi-directional; the causality from public expenditure to output along Keynesian lines was limited.
Keywords: C23; E60; H50; N44; 330; Wagner's hypothesis; panel cointegration; panel causality; Europe